P-C23 Spleen tyrosine kinase (Syk) controls IFN-α production inhibited in plasmacytoid dendritic cells by surface glycoproteins of HIV, HBV and HCV. (March 2017) - Aouar, Besma; Kovarova, Denisa; Font-Haro, Albert; Weber, Jan; Durantel, David; Trejbalova, Katerina; Hejnar, Jiri; Nunes, Jacques; Olive, Daniel; Dubreuil, Patrice; Hirsch, Ivan; Stranska, Ruzena
Abstract : Crosslinking of regulatory immunoreceptors, such as BDCA-2 (CD303) or ILT7 (CD85g), of plasmacytoid dendritic cells (pDCs) efficiently suppresses production of type-I interferon (IFN)-α/β and other cytokines in response to Toll-like receptor (TLR) 7/9 ligands. Viral surface glycoproteins, HIV-1 gp120, hepatitis C virus (HCV) E2 and hepatitis B virus (HBV) HBsAg were shown to be ligands of pDC regulatory immunoreceptors. Cytokine-inhibitory pathway triggered by ligation of regulatory immunoreceptors is mediated by spleen tyrosine kinase (Syk) associated with the ITAM-containing adapter of regulatory immunoreceptors. Here we demonstrate by pharmacological targeting of Syk that in addition to the negative regulation of TLR7/9 signaling via regulatory immunoreceptors, Syk also positively regulates the TLR7/9 pathway in human pDCs. Novel highly specific Syk inhibitor AB8779 suppressed IFN-α, TNF-α and IL-6 production induced by TLR7/9 agonists in primary pDCs and in the pDC cell line GEN2.2. Triggering of TLR9 or regulatory immunoreceptors signaling induced a differential kinetics of phosphorylation at Y352 and Y525/526 of Syk and a differential sensitivity to AB8779. Consistent with the different roles of Syk in TLR7/9 and regulatory immunoreceptors signaling, a concentration of AB8779 insufficient to block TLR7/9 signaling still released the block of IFN-α production triggered via the regulatory immunoreceptor pathway, including that induced by HIV, HBV and HCV. Thus, pharmacological targeting of Syk partially restored the main pDC function—IFN-α production. Opposing roles of Syk in TLR7/9 and regulatory immunoreceptor pathways may regulate the innate immune response to weaken inflammation reaction.